Relationship between exhaled nitric oxide and mucosal eosinophilic inflammation in mild to moderately severe asthma. Issue 3 (1st March 2000) - Lim, Sam; Jatakanon, Anon; Meah, Sally; Oates, Timothy; Chung, Kian Fan; Barnes, Peter J
Abstract : BACKGROUND: Exhaled levels of nitric oxide (NO) are raised in asthma but the relationship between exhaled NO levels and a direct measure of airway inflammation has not been investigated in asthmatic patients treated with inhaled steroids. METHODS: The relationship between exhaled NO levels, clinical measures of asthma control, and direct markers of airway inflammation were studied in patients with asthma treated with and without inhaled corticosteroids. Thirty two asthmatic patients (16 not using inhaled steroids and 16 using inhaled beclomethasone dipropionate, 400–1000 μg/day) were monitored with respect to measures of asthma control including lung function, symptom scores, medication usage, and variability of peak expiratory flow (PEF) for one month. Measurements of exhaled NO and fibreoptic bronchoscopy were performed at the end of the monitoring period. Bronchial mucosal biopsy specimens were stained with an anti-MBP antibody for quantification of eosinophils. RESULTS: There was no significant difference in lung function, symptom scores, or medication usage between the two groups, but there was a significant difference in PEF variability (8.7 (1.2)% in steroid naive patients versus 13.6 (1.9)% in steroid treated patients, p<0.05) and exhaled NO levels (9.9 (3.5) ppb in steroid naive patients versus 13.6 (2.0) ppb in steroid treated patients, p<0.05). There was no correlation between exhaled NO and mucosal eosinophils, or between NO and conventional measures of asthma control. There was a significant correlation between mucosal eosinophils and lung function ( r = –0.43, p<0.05). CONCLUSIONS: Exhaled NO levels do not reflect airway mucosal eosinophilia and these markers reflect different aspects of airway inflammation. The clinical usefulness of exhaled NO needs to be determined in prospective longitudinal studies.